PENGARUH KEMAMPUAN MANAJERIAL GURU, DISIPLIN KERJA GURU, DAN KOMPETENSI GURU TERHADAP KINERJA GURU MA AL-MIFTAH KECAMATAN PASEAN KABUPATEN PAMEKASAN - jurnalmap map; Ali Maksum; Nugroho Mawardi Wibowo; Muninghar ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This research was conducted at the ma al-miftah kecamatan pasean kabupaten pamekasan with a total sample of 48 people. The results showed that managerial capabilities simultaneously, teacher, the discipline of work and competence of teachers teachers had a very significant influence on performance Teacher, evidenced by the value of F is calculated with a degree of 3,135 the significance of 0.003 (less than 0.05). Partially, the managerial capabilities of the teacher, discipline and competence of teachers teacher's work has a significant influence on performance teacher on ma al-miftah kecamatan pasean kabupaten pamekasan. Keywords: Managerial abilities of teachers (X1), Discipline of work teachers (X2), Competence of teachers (X3) and Performance of the teacher (Y)